Modified graphite negative electrode material and preparation method thereof

By pre-oxidizing the graphite and using amphiphilic carbon material to coat and modify it, the modified graphite negative electrode material with core-shell structure is solved, and the problem of insufficient fast charging and cycling performance of graphite negative electrode material is achieved, and high capacity and Excellent electrochemical properties.

CN119390065APending Publication Date: 2025-02-07HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411551908.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The high graphitized crystallinity and high orientation layer structure of graphite negative electrode materials limit the deintercalation and transmission speed of lithium ions, affect fast charging performance, and lead to irreversible capacity loss and reduced cycle life.

Method used

The number of oxygen-containing functional groups on the surface is increased by pre-oxidizing the graphite, and then it is coated and modified with an amphiphilic carbon material that is both hydrophilic and lipophilic to form a modified graphite negative electrode material with a core-shell structure.

Benefits of technology

The modified graphite anode material has high capacity, low potential platform and excellent fast charging and cycling performance. At the same time, the process is simple, green and environmentally friendly, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390065A_ABST
    Figure CN119390065A_ABST
Patent Text Reader

Abstract

The invention provides a modified graphite negative electrode material and a preparation method thereof.The preparation method comprises the steps that an amphiphilic carbon material solution and pre-oxidized graphite are mixed, kneaded, dried and subjected to heat treatment, and a modified graphite negative electrode material precursor is obtained; and carrying out carbonization treatment on the modified graphite negative electrode material precursor to obtain the modified graphite negative electrode material. The number of oxygen-containing functional groups on the surface of the graphite is increased by performing pre-oxidation treatment on the graphite, the affinity between the graphite and the amphiphilic carbon material is increased, and the prepared modified graphite negative electrode material has the advantages of high capacity, low potential platform and the like, and also has excellent fast charging performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the technical field of electrode material preparation, and in particular to a modified graphite negative electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have been widely used in new energy and other fields due to their high energy density and good cycle performance. Graphite negative electrode materials have the characteristics of high specific capacity and environmental friendliness, and have become one of the most commonly used negative electrode materials on the market. However, the high crystallinity of graphite and the highly oriented graphite layered structure limit the deintercalation and transmission speed of lithium ions between graphite negative electrode sheets, which in turn affects its fast charging performance. The insertion and deintercalation of lithium ions between graphite sheets will cause the volume of graphite sheets to expand and contract, which will cause the pulverization of graphite, and ultimately cause irreversible capacity loss and reduce its cycle life. Summary of the invention

[0003] In view of this, the present application provides a modified graphite negative electrode material and a preparation method thereof, wherein the preparation method increases the number of oxygen-containing functional groups on the surface of the graphite by pre-oxidation treatment, and then uses an amphiphilic carbon material that is both hydrophilic and lipophilic to coat and modify the graphite. The oxygen-rich graphite has good affinity with the amphiphilic carbon material. The prepared modified graphite negative electrode material is a core-shell structure, in which the amphiphilic carbon material coating layer is uniformly coated and has a strong bonding force with the graphite core. The modified graphite negative electrode material has the advantages of high capacity and low potential platform, and also has excellent fast charging performance and cycle performance.

[0004] The first aspect of the present application provides a method for preparing a modified graphite negative electrode material, comprising:

[0005] The amphiphilic carbon material solution and pre-oxidized graphite are kneaded, dried, and heat-treated to obtain a modified graphite negative electrode material precursor;

[0006] The modified graphite negative electrode material precursor is carbonized to obtain the modified graphite negative electrode material.

[0007] In the implementation manner of the present application, the oxygen content in the pre-oxidized graphite is 3%-10%.

[0008] In the embodiment of the present application, the mass of the amphiphilic carbon material in the amphiphilic carbon material solution is 1.5%-3% of the mass of the pre-oxidized graphite.

[0009] In an embodiment of the present application, the method for preparing the pre-oxidized graphite includes: pre-oxidizing graphite to obtain pre-oxidized graphite;

[0010] The pre-oxidation treatment includes gas phase pre-oxidation treatment or liquid phase pre-oxidation treatment.

[0011] In the embodiment of the present application, the temperature of the gas phase pre-oxidation treatment is 600° C.-700° C., and the time of the gas phase pre-oxidation treatment is 30 min-60 min.

[0012] In the embodiment of the present application, the flow rate of the oxidizing gas in the gas-phase pre-oxidation treatment is 100 mL / min-200 mL / min, and the oxidizing gas includes one or more of air, oxygen and ozone.

[0013] In the embodiment of the present application, the temperature of the liquid phase pre-oxidation treatment is 20° C.-40° C., and the time of the liquid phase pre-oxidation treatment is 30 min-60 min.

[0014] In the embodiment of the present application, the oxidant of the liquid phase pre-oxidation treatment includes one or more of concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide and perchloric acid.

[0015] In the embodiment of the present application, the particle size D50 of the graphite is 7 μm-15 μm; and / or the specific surface area of ​​the graphite is 1.0 m 2 / g-3.0m 2 / g.

[0016] In the implementation manner of the present application, the kneading is carried out at room temperature, and the kneading time is 1-2h.

[0017] In the embodiment of the present application, a drying step is further included after the kneading and before the heat treatment.

[0018] In the embodiment of the present application, the drying temperature is 150° C.-180° C., and the drying time is 2 h-3 h.

[0019] In the embodiment of the present application, the heat treatment is a two-stage heat treatment; the temperature of the first stage of the two-stage heat treatment is 200℃-250℃, and the time is 2h-3h; the temperature of the second stage of the two-stage heat treatment is 500℃-550℃, and the time is 1h-2h.

[0020] In the embodiment of the present application, the temperature of the carbonization treatment is 1000° C.-1200° C., and the time of the carbonization treatment is 6 h-8 h.

[0021] In an embodiment of the present application, the raw materials for preparing the amphiphilic carbon material include one or more of pitch coke, petroleum coke and needle coke.

[0022] The second aspect of the present application provides a modified graphite negative electrode material obtained by the preparation method provided in the first aspect, wherein the modified graphite negative electrode material is a core-shell structure, including a graphite core and an amphiphilic carbon material coating layer coated on the surface of the graphite core.

[0023] In the embodiment of the present application, the particle size D50 of the modified graphite negative electrode material is 10 μm-20 μm; and / or the specific surface area of ​​the modified graphite negative electrode material is 1 m 2 / g-2m 2 / g.

[0024] The third aspect of the present application provides a battery negative electrode, including a current collector and a negative electrode active layer loaded on the current collector, wherein the negative electrode active layer includes a modified graphite negative electrode material prepared by the preparation method described in the first aspect or the modified graphite negative electrode material described in the second aspect of the present application.

[0025] A fourth aspect of the present application provides a battery, comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, wherein the negative electrode comprises the battery negative electrode as described in the third aspect.

[0026] A fifth aspect of the present application provides an electrical device, wherein the electrical device comprises the battery as described in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A flow chart of a method for preparing a modified graphite negative electrode material provided in an embodiment of the present application;

[0028] Figure 2 A schematic diagram of the cross-sectional structure of a modified graphite negative electrode material provided in an embodiment of the present application;

[0029] Figure 3 This is a HRTEM (High Resolution Transmission Electron Microscope) photograph of the amphiphilic carbon material coating layer of the modified graphite negative electrode material provided in one embodiment of the present application.

[0030] Description of Figure Numbers

[0031] 100-modified graphite negative electrode material; 101-graphite core; 102-amphiphilic carbon material coating layer. DETAILED DESCRIPTION

[0032] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.

[0033] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.

[0034] Graphite negative electrode materials have the characteristics of high specific capacity and environmental friendliness, and have become one of the most commonly used negative electrode materials on the market. However, the high graphitization crystallinity of graphite and the highly oriented graphite layered structure affect its electrochemical performance. The highly oriented lamellar structure of graphite will cause lithium ions to be inserted into the graphite lamellar layers together with organic solvents during the embedding process. When the organic solvent between the graphite lamellar layers is reduced, gas will be generated, which will cause the graphite lamellar layers to peel off. The insertion and deintercalation of lithium ions between the graphite lamellar layers will cause the volume of the graphite lamellar layers to expand and shrink, causing the graphite to pulverize, which will seriously affect the capacity and cycle life of the graphite negative electrode material. In addition, the lamellar structure of graphite will limit and hinder the deintercalation and transmission speed of lithium ions, thereby affecting its fast charging performance. In order to alleviate the above-mentioned problems of graphite negative electrode materials, it is common practice to coat and modify graphite. However, the existing methods have problems such as expensive raw materials, uneven coating, unsuitable for large-scale mass production, and easy to cause environmental pollution.

[0035] In response to the above problems, the present application provides a modified graphite negative electrode material and a preparation method thereof. The preparation method increases the number of oxygen-containing functional groups on the surface of graphite by pre-oxidation treatment, and then uses an amphiphilic carbon material that is both hydrophilic and lipophilic to coat and modify the graphite. The oxygen-rich graphite has good affinity with the amphiphilic carbon material. The prepared modified graphite negative electrode material is a core-shell structure, in which the amphiphilic carbon material coating layer is uniformly coated and has a strong bonding force with the graphite core. The modified graphite negative electrode material has the advantages of high capacity and low potential platform, and also has excellent fast charging performance and cycle performance.

[0036] The present application provides a method for preparing a modified graphite negative electrode material. Figure 1 The flowchart of the preparation method comprises:

[0037] S101, mixing, drying and heat treating the amphiphilic carbon material solution and pre-oxidized graphite to obtain a modified graphite negative electrode material precursor;

[0038] S102, carbonizing the modified graphite negative electrode material precursor to obtain a modified graphite negative electrode material.

[0039] In the embodiment of the present application, amphiphilic carbonaceous material (ACM) refers to a special carbon material with both hydrophilicity and lipophilicity that is soluble in alkaline solution or certain organic solvents, obtained by oxidation, nitration or sulfonation of carbon materials such as asphalt and green coke (petroleum coke, needle coke).

[0040] In step S101, the pre-oxidized graphite can be obtained by pre-oxidizing graphite. In the embodiment of the present application, the graphite can be artificial graphite or natural graphite. In the embodiment of the present application, the particle size D50 of the graphite is 7 μm-15 μm; the specific surface area of ​​the graphite is 1.0 m 2 / g-3.0m 2 In some specific embodiments of the present application, the particle size D50 of graphite can be, for example, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, and the specific surface area of ​​graphite can be, for example, 1.0 m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 3m 2 / g. In the present application, particle size D50 refers to the median particle size, that is, the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. The present application can further improve the degree of pre-oxidation by controlling the particle size and specific surface area of ​​graphite within the relevant range, thereby improving the active sites of oxygen-containing functional groups grafted on its surface, and making these oxygen-containing functional groups uniformly dispersed on the surface of graphite, so as to facilitate the subsequent ACM to form a uniform coating layer on the graphite surface. In the present application, the particle size D50 can be measured by a laser particle size analyzer; the specific surface area can be tested by a specific surface and porosity analyzer, and the test standard refers to the national standard GB / T 19587-2017.

[0041] In an embodiment of the present application, the pre-oxidation treatment includes a gas phase pre-oxidation treatment or a liquid phase pre-oxidation treatment. In some embodiments, the pre-oxidation treatment is a gas phase pre-oxidation treatment. In an embodiment of the present application, the temperature of the gas phase pre-oxidation treatment is 600°C-700°C, and the time of the gas phase pre-oxidation treatment is 30min-60min. In some specific embodiments, the temperature of the gas phase pre-oxidation treatment can be, for example, 600°C, 620°C, 640°C, 650°C, 660°C, 680°C, 700°C, and the time of the gas phase pre-oxidation treatment can be, for example, 30min, 35min, 40min, 45min, 50min, 55min, 60min. The present application can further control the number of oxygen-containing functional groups on the graphite surface by controlling the temperature and time of the gas phase pre-oxidation treatment within a suitable range.

[0042] In some specific embodiments of the present application, the gas phase pre-oxidation treatment can be, for example, placing natural graphite in a chemical vapor deposition (CVD) furnace tube, passing an oxidizing gas, and heating the graphite for pre-oxidation. In other specific embodiments of the present application, the pre-oxidation treatment can also be carried out by liquid phase oxidation using an oxidant such as concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide or perchloric acid. In the embodiments of the present application, the oxidizing gas includes one or more of air, oxygen and ozone. In some specific embodiments, the oxidizing gas can be, for example, air, oxygen or ozone. In other embodiments, the oxidizing gas can be, for example, a mixed gas of oxygen or ozone and nitrogen.

[0043] In the embodiment of the present application, the flow rate of the oxidizing gas for gas phase pre-oxidation treatment is 100mL / min-200mL / min. In some specific embodiments, the flow rate of the oxidizing gas for gas phase pre-oxidation treatment can be, for example, 100mL / min, 120mL / min, 140mL / min, 150mL / min, 160mL / min, 180mL / min, 200mL / min. The present application can further control the degree of pre-oxidation of graphite by controlling the air flow rate of the pre-oxidation treatment within the above range, thereby controlling the number of oxygen-containing functional groups on the graphite surface to within the actual required range, thereby improving the bonding force between the graphite core and the ACM coating layer.

[0044] In other embodiments of the present application, the pre-oxidation treatment is a liquid phase pre-oxidation treatment. In the embodiment of the present application, the temperature of the liquid phase pre-oxidation treatment is 20°C-40°C, and the time of the liquid phase pre-oxidation treatment is 30min-60min. In some specific embodiments, the temperature of the liquid phase pre-oxidation treatment can be, for example, 20°C, 25°C, 30°C, 35°C, 40°C, and the time of the liquid phase pre-oxidation treatment can be, for example, 30min, 35min, 40min, 45min, 50min, 55min, 60min. The present application can further control the number of oxygen-containing functional groups on the graphite surface by controlling the temperature and time of the liquid phase pre-oxidation treatment within a suitable range. In the embodiment of the present application, the oxidant for the liquid phase pre-oxidation treatment includes one or more of concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide and perchloric acid. The present application can graft oxygen-containing functional groups on the graphite surface by pre-oxidation treatment of graphite. These oxygen-containing functional groups on the graphite surface will be mutually compatible with the functional groups on the ACM surface, effectively improving the bonding force between the graphite core and the ACM coating.

[0045] In the embodiment of the present application, the oxygen content in the pre-oxidized graphite is 3%-10%. In some specific embodiments, the oxygen content in the pre-oxidized graphite can be, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%. The present application can further control the number of oxygen-containing functional groups on the graphite surface by controlling the oxygen content in the pre-oxidized graphite within a suitable range, thereby avoiding the problem of poor affinity with ACM caused by too low oxygen content and the problem of graphite itself being destroyed and affecting its electrochemical performance due to too high oxygen content to a certain extent. In the present application, the oxygen content in the pre-oxidized graphite can be measured by scanning electron microscope-energy dispersive spectrometer (Scanning Electron Microscope-Energy Dispersive Spectrometer, SEM-EDS).

[0046] In the embodiment of the present application, the mass of ACM in the amphiphilic carbon material solution is 1.5%-3% of the mass of the pre-oxidized graphite. In some specific embodiments, the mass of ACM in the amphiphilic carbon material solution can be, for example, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.5%, 2.6%, 2.8%, 3% of the mass of the pre-oxidized graphite. The present application controls the feed ratio of ACM and pre-oxidized graphite within a suitable range, which can ensure that ACM forms a complete, uniform, and moderately thick coating on the surface of the pre-oxidized graphite particles on the one hand, and can alleviate the problem of agglomeration due to too much ACM and the inability to form a coating to a certain extent on the other hand.

[0047] In an embodiment of the present application, an amphiphilic carbon material solution can be obtained by dissolving ACM in a solvent. In some embodiments of the present application, ACM can be obtained by preparation, and the raw materials for preparing ACM include but are not limited to one or more of asphalt coke, petroleum coke and needle coke. In some specific embodiments of the present application, the raw material for preparing ACM can be, for example, petroleum coke tail powder with a particle size less than or equal to 5 μm. By selecting a carbon material with a smaller particle size as the raw material for preparing ACM, the oxidation degree of the obtained ACM can be further improved, thereby further improving the subsequent coating uniformity of graphite and the bonding force between the ACM coating layer and the graphite core.

[0048] In some specific embodiments of the present application, the process of preparing ACM includes:

[0049] S201, mixing petroleum coke tail powder with concentrated sulfuric acid, adding concentrated nitric acid dropwise, performing a first mixing treatment, washing and drying to obtain an ACM precursor;

[0050] S202, dissolving the ACM precursor in a sodium hydroxide solution, performing a second mixing treatment, collecting the upper liquid after sedimentation, and obtaining an ACM precursor solution;

[0051] S203, adding hydrochloric acid to the ACM precursor solution, washing and drying to obtain ACM.

[0052] In step S201, the particle size of the petroleum coke tail powder is less than or equal to 5 μm. In some specific embodiments of the present application, the particle size of the petroleum coke tail powder can be, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm. In the present application, petroleum coke refers to the vacuum residue of petroleum, which is cracked and coked at 500°C-550°C in a coking unit to generate black solid coke; petroleum coke tail powder refers to industrial waste generated in the powder production process when the oil coke is used downstream. The particle size of petroleum coke tail powder is usually small and the powder is very fine. It is impossible to use conventional processes to produce qualified products in the future. It is usually regarded as industrial waste and discarded. The present application collects petroleum coke tail powder as a raw material for preparing amphiphilic carbon materials. On the one hand, it can effectively improve the utilization rate of petroleum coke in the production and preparation process, avoid the waste of valuable tail powder, and effectively reduce the raw material cost of amphiphilic carbon materials while being green and environmentally friendly. On the other hand, the powder of petroleum coke tail powder is fine. The present application can effectively increase the contact area and active sites of the oxidation reaction of petroleum coke tail powder by selecting petroleum coke tail powder with a particle size of less than or equal to 5μm, effectively improve the oxidation degree of ACM prepared using it, and thereby improve the subsequent ACM coating uniformity of graphite and the bonding force between the ACM coating layer and the graphite core.

[0053] In the embodiment of the present application, the specific surface area of ​​the petroleum coke tail powder is 20m 2 / g-50m 2 In some specific embodiments of the present application, the specific surface area of ​​the petroleum coke tail powder can be, for example, 20 m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g. The present application can further increase the contact area and active sites of the oxidation reaction by controlling the specific surface area of ​​the petroleum coke tail powder within a suitable range, thereby further increasing the oxidation degree of ACM.

[0054] In the embodiment of the present application, the concentration of concentrated sulfuric acid is 96%-99%, and the concentration of concentrated nitric acid is 65%-68%. In some specific embodiments of the present application, the concentration of concentrated sulfuric acid can be, for example, 96%, 97%, 98%, 99%, and the concentration of concentrated nitric acid can be, for example, 65%, 66%, 67%, 68%. In the embodiment of the present application, the solid-liquid ratio of the mixed solution of petroleum coke tail powder and concentrated sulfuric acid and concentrated nitric acid is 1g: (7mL-10mL). In some specific embodiments, the solid-liquid ratio of the mixed solution of petroleum coke tail powder and concentrated sulfuric acid and concentrated nitric acid can be, for example, 1g: 7mL, 1g: 8mL, 1g: 9mL, 1g: 10mL. The main component of petroleum coke is a polycyclic aromatic compound. This application uses a mixed acid system of concentrated sulfuric acid and concentrated nitric acid to prepare an amphiphilic carbon material. The system will undergo a series of oxidation reactions such as nitration and sulfonation reactions at the side chains or edges of the polycyclic aromatic compound molecules, introducing functional groups such as -NO2 and -SO3H. These functional groups provide hydrophilicity for the amphiphilic carbon material, which is conducive to promoting the dissolution of ACM in subsequent alkaline solutions. This application controls the concentration of each component in the mixed acid system of concentrated sulfuric acid and concentrated nitric acid within a suitable range. On the one hand, it can effectively control the reaction rate of the system and slow down the heating rate caused by the excessive reaction. On the other hand, it can further improve the utilization rate of petroleum coke tail powder. The particle size of the petroleum coke tail powder used to prepare ACM in this application is small, and there are more reactive sites. Therefore, the solid-liquid ratio of the corresponding petroleum coke tail powder to the mixed solution of concentrated sulfuric acid and concentrated nitric acid is also low, that is, the petroleum coke tail powder can be oxidized with less acidic solution to prepare the ACM precursor, further reducing the preparation cost of ACM.

[0055] In the implementation manner of the present application, the volume of concentrated sulfuric acid accounts for 70%-90% of the sum of the volumes of concentrated sulfuric acid and concentrated nitric acid. In some specific implementation manners of the present application, the volume of concentrated sulfuric acid can account for 70%, 75%, 80%, 85%, 90% of the sum of the volumes of concentrated sulfuric acid and concentrated nitric acid. The present application can effectively play the role of concentrated sulfuric acid as an oxidant for sulfonation reaction and a catalyst for nitration reaction by controlling the content ratio of concentrated sulfuric acid and concentrated nitric acid within the above range, and can also ensure its role as a dehydrating agent for the mixed acid system of concentrated sulfuric acid and concentrated nitric acid to a certain extent, thereby obtaining a more stable mixed acid system that is more conducive to the reaction.

[0056] In the embodiment of the present application, the concentrated nitric acid is added dropwise. By controlling the concentrated nitric acid to be added dropwise, the reaction speed and temperature of the system can be further controlled, and the violent reaction of the system caused by the small particle size of the petroleum coke tail powder can be effectively alleviated.

[0057] In the embodiment of the present application, the temperature of the first mixing treatment is 50°C-80°C, and the time of the first mixing treatment is 1h-3h. In some specific embodiments, the temperature of the first mixing treatment can be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and the time of the first mixing treatment can be, for example, 1h, 1.5h, 2h, 2.5h, 3h. The present application can further improve the hydrophilicity of the prepared ACM precursor by controlling the parameters of the first mixing treatment within a suitable range.

[0058] In the embodiment of the present application, the washing and drying method in step S201 can specifically be filtering through a Buchner funnel and then washing with deionized water until the filtrate is neutral.

[0059] In step S202, the concentration of sodium hydroxide is 0.5mol / L-1.5mol / L. In some specific embodiments, the concentration of sodium hydroxide can be, for example, 0.5mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.5mol / L. The present application can fully dissolve the ACM precursor by controlling the concentration of sodium hydroxide within a suitable range, thereby further improving the yield of ACM.

[0060] In an embodiment of the present application, the temperature of the second mixing treatment is 50°C-80°C, and the time of the second mixing treatment is 1h-3h. In some specific embodiments, the temperature of the second mixing treatment can be, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, and the time of the second mixing treatment can be, for example, 1h, 1.5h, 2h, 2.5h, 3h. In some embodiments of the present application, the pH of the system after the second mixing treatment is greater than 12. The present application can further increase the solubility of the obtained ACM precursor in the sodium hydroxide solution by controlling the parameters of the second mixing treatment within a suitable range.

[0061] In step S203, the concentration of hydrochloric acid is 0.5mol / L-1.5mol / L. In some specific embodiments, the concentration of hydrochloric acid can be, for example, 0.5mol / L, 0.6mol / L, 0.8mol / L, 1mol / L, 1.2mol / L, 1.4mol / L, 1.5mol / L. The present application can effectively neutralize the pH value of the system by adding a suitable concentration of hydrochloric acid to the alkaline ACM precursor solution, thereby obtaining a neutral ACM product.

[0062] In the embodiment of the present application, the washing and drying method in step S203 can specifically be filtering with a Buchner funnel, washing with deionized water until the filtrate is neutral, and then drying.

[0063] In the embodiment of the present application, the particle size D50 of ACM is 5μm-8μm. In some specific embodiments, the particle size D50 of ACM can be, for example, 5μm, 6μm, 7μm, 8μm. The present application uses petroleum coke tail powder as a raw material and controls the reaction conditions within a suitable range to produce ACM particles with a particle size within the above range, which is further beneficial to the subsequent coating of graphite particles and improves the uniformity of the ACM coating layer.

[0064] In the embodiment of the present application, the kneading time is 1h-2h, and the kneading temperature is 20℃-30℃. In some specific embodiments, the kneading time can be, for example, 1h, 1.5h, 2h, and the kneading temperature can be, for example, 20℃, 22℃, 25℃, 26℃, 28℃, 30℃. Controlling the parameters of the kneading process within the above range can make the pre-oxidized graphite particles and the ACM solution fully and evenly mixed, thereby further improving the subsequent ACM coating uniformity of the pre-oxidized graphite particles. ACM is amphiphilic, both hydrophilic and lipophilic. Therefore, ACM molecules can form a self-assembled coating layer at the interface between water and pre-oxidized graphite to make up for the defects of the graphite layered structure, thereby effectively promoting the deintercalation and transmission of lithium ions in the negative electrode material, and at the same time, it can also limit the volume expansion of graphite, and improve the fast charging performance and cycle performance of the modified graphite negative electrode material.

[0065] In the embodiment of the present application, the heat treatment is a two-stage heat treatment. In the embodiment of the present application, the temperature of the first stage of the two-stage heat treatment is 200°C-250°C, and the time is 2h-3h. In some specific embodiments, the temperature of the first stage of the heat treatment can be, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, and the time can be, for example, 2h, 2.5h, 3h. In the embodiment of the present application, the temperature of the second stage of the two-stage heat treatment can be, for example, 500°C-550°C, and the time can be, for example, 1h-2h. The present application can effectively slow down the volatilization and aromatization reaction process of the ACM coating by adopting a two-stage heat treatment, thereby avoiding to a certain extent the aromatization reaction of the ACM coating agent before being mixed evenly due to the rapid heating of the heat treatment process, reducing the possibility of ACM forming graphite flakes alone, and thus improving the coating uniformity of ACM on the graphite surface. In the present application, the relevant parameters of the two-stage heat treatment are controlled within a suitable range, which can further improve the uniformity of ACM coating on graphite and the direct bonding strength between ACM and graphite.

[0066] In step S102, the temperature of the carbonization treatment is 1000°C-1200°C, and the time of the carbonization treatment is 6h-8h. In some specific embodiments, the temperature of the carbonization treatment can be, for example, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and the time of the carbonization treatment can be, for example, 6h, 6.5h, 7h, 7.5h, 8h. Controlling the parameters of the carbonization treatment within the above-mentioned appropriate range can further control the surface performance parameters such as the porosity and specific surface area of ​​the obtained modified graphite negative electrode material, thereby obtaining a negative electrode material with high capacity and good fast charging performance and cycle performance.

[0067] The preparation method of the modified graphite composite negative electrode material provided in the present application adopts an amphiphilic carbon material that is both hydrophilic and lipophilic to coat and modify the graphite that has been pre-oxidized. After the graphite is pre-oxidized, oxygen-containing functional groups are grafted on the surface. The amphiphilic carbon material has good affinity with the pre-oxidized graphite, and the amphiphilic carbon material coating layer of the prepared modified graphite negative electrode material is uniform. The modified graphite negative electrode material prepared by this method has the advantages of high capacity and low potential platform of graphite itself. The coating of the amphiphilic carbon material also effectively compensates for the defects caused by the graphite sheet structure and effectively alleviates the volume expansion problem of graphite during the charging and discharging process, thereby significantly improving its fast charging performance and cycle performance. In addition, the preparation method is simple in process and does not require the use of organic solvents in the preparation process. It is green and environmentally friendly and suitable for large-scale industrial production.

[0068] The present application also provides a modified graphite negative electrode material prepared by the preparation method provided above. The cross-sectional structure diagram of the modified graphite negative electrode material is as follows: Figure 2As shown, the modified graphite negative electrode material 100 is a core-shell structure, including a graphite core 101 and an amphiphilic carbon material coating layer 102 coated on the surface of the graphite core 101. In the present application, the amphiphilic carbon material coating layer 102 coats the graphite core 101 having a lamellar structure, which can effectively coat the edges of the graphite lamellae, make up for the defects of the graphite lamellae structure, promote the deintercalation and transmission speed of lithium ions between the graphite lamellae, and thus improve the fast charging performance of the modified graphite negative electrode material. In addition, the coating of the graphite core 101 by the amphiphilic carbon material coating layer 102 can also effectively prevent organic solvents from entering the lamellar space of graphite and effectively limit the volume expansion of graphite, thereby avoiding the graphite lamellae from falling off or pulverizing to a certain extent, and improving the capacity and cycle life of the modified graphite negative electrode material. Compared with other carbon materials, the amphiphilic carbon material is both hydrophilic and oleophilic, has good bonding with graphite, and the obtained amphiphilic carbon material coating layer 102 is evenly coated. In the present application, the coating uniformity of the coating layer of the graphite negative electrode material can be reflected by the confocal Raman distribution value measured by the confocal Raman spectrometer. The smaller the value, the better the coating uniformity of the corresponding coating layer. Specifically, the confocal Raman distribution value is to use the confocal Raman spectrometer to test 2500 positions of each sample, and output the Raman values ​​I at 10%, 50%, and 90% respectively. 10 ,I 50 ,I 90 , confocal Raman distribution value = (I 90 -I 10 ) / I 50 In some specific embodiments of the present application, the amphiphilic carbon material coating layer 102 is as follows: Figure 3 As shown, Figure 3 This is a HRTEM (High Resolution Transmission Electron Microscope) photo of the amphiphilic carbon material coating layer of the modified graphite negative electrode material of an embodiment of the present application, from Figure 3 It can be seen that the amphiphilic carbon material coating layer is a three-dimensional porous structure built by the accumulation of carbon sheets.

[0069] In the embodiment of the present application, the particle size D50 of the modified graphite negative electrode material is 10 μm-20 μm. In some specific embodiments of the present application, the particle size D50 of the modified graphite negative electrode material can be, for example, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm. In the embodiment of the present application, the specific surface area of ​​the modified graphite negative electrode material is 1 m 2 / g-2m 2 In some specific embodiments of the present application, the specific surface area of ​​the modified graphite negative electrode material can be, for example, 1 m 2 / g, 1.2m 2 / g, 1.4m2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2m 2 / g.

[0070] The modified graphite negative electrode material provided in the present application uses an amphiphilic carbon material to coat graphite, and the obtained coating layer has a strong bonding force with the graphite and a uniform thickness. While having the advantages of high capacity and low potential platform of graphite itself, the modified graphite negative electrode material also has good fast charging performance and cycle performance.

[0071] The present application also provides a battery negative electrode, including a current collector and a negative electrode active layer loaded on the current collector, the negative electrode active layer including a modified graphite negative electrode material prepared by the preparation method as described above or a modified graphite negative electrode material provided above. In the embodiment of the present application, the current collector includes but is not limited to any one of copper foil and foam copper. In some embodiments of the present application, the negative electrode active layer also includes a conductive agent, an adhesive, etc. In the embodiment of the present application, the conductive agent can be any conductive agent known in the art. In some embodiments of the present application, the conductive agent can be, for example, one or more of super carbon black, acetylene black, graphene, and carbon nanotubes. In the embodiment of the present application, the adhesive can be any adhesive known in the art. In some embodiments of the present application, the adhesive can be, for example, one or more of sodium hydroxycellulose, polyvinylidene fluoride, and styrene-butadiene rubber.

[0072] The present application also provides a battery, the battery comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, the negative electrode comprising the battery negative electrode provided above. In the embodiment of the present application, the positive electrode comprises a positive electrode active layer, and the positive electrode active material in the positive electrode active layer is any positive electrode active material known in the art, including but not limited to modified or unmodified lithium iron phosphate, lithium iron manganese phosphate, ternary positive electrode material (such as NCM ternary or NCA ternary), binary positive electrode material, etc.

[0073] The present application also provides an electric device, which includes the battery provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.

[0074] The present application is further described below in multiple embodiments:

[0075] Example 1

[0076] (1) 40 g of petroleum coke tail powder with a particle size D50 of 5 μm was taken as a raw material and added to 280 mL of concentrated sulfuric acid with a concentration of 98% and mixed evenly, and then 120 mL of concentrated nitric acid with a concentration of 65% was taken and the concentrated nitric acid was added dropwise to the mixture of the petroleum coke tail powder and concentrated sulfuric acid with a dropper; the temperature was raised to 80° C. and stirred for reaction for 3 h. After the reaction was completed, the reactant was poured into 1000 mL of deionized water to terminate the reaction; then the reaction was filtered and washed with deionized water until the filtrate had a pH value of 2-3 to obtain an ACM precursor;

[0077] The ACM precursor was mixed with 1000 mL of a 1 mol / L sodium hydroxide solution, stirred at 80° C. for 1 h to dissolve, and the solution was precipitated and the upper layer of liquid was collected to obtain an ACM precursor solution;

[0078] Add 1000 mL of 1 mol / L hydrochloric acid solution to the ACM precursor solution, adjust the pH value to less than 2, filter with a Buchner funnel, wash with deionized water until neutral, collect the solid matter, and then dry at 100°C to obtain ACM;

[0079] (2) taking 500 g of natural graphite with a particle size D50 of 9 μm, placing it in a CVD tube furnace for pre-oxidation treatment, introducing air at a flow rate of 100 mL / min, heating it to 600° C. at 3° C. / min, keeping it warm for 30 min, cooling it naturally to the rising temperature, and taking it out to obtain pre-oxidized graphite;

[0080] (3) 20 g of the prepared ACM was dissolved in water to obtain an ACM solution, and the ACM solution and 500 g of pre-oxidized graphite were added to a kneading pot, kneaded at 25° C. for 2 h, heated to 150° C., and stirred for 2 h to obtain a kneaded material; the kneaded material was added to a converter for a two-stage heat treatment: first, treated at 250° C. for 2 h, and then heated to 500° C. for 1 h to obtain a modified graphite negative electrode material precursor;

[0081] (4) The modified graphite negative electrode material precursor is carbonized at 1150° C. to obtain a modified graphite negative electrode material.

[0082] Example 2

[0083] The only difference from Example 1 is that the petroleum coke tail powder in step (1) is replaced by conventional petroleum coke powder, and D50 is 10 um.

[0084] Example 3

[0085] The only difference from Example 1 is that the natural graphite in step (2) is replaced by artificial graphite.

[0086] Example 4

[0087] The only difference from Example 1 is that the temperature of the pre-oxidation treatment in step (2) is 650°C.

[0088] Example 5

[0089] The only difference from Example 1 is that the pre-oxidation treatment time in step (2) is 45 minutes.

[0090] Example 6

[0091] The only difference from Example 1 is that the pre-oxidation treatment time in step (2) is 10 minutes.

[0092] Example 7

[0093] The only difference from Example 1 is that step (2) is: 500 g of natural graphite with a particle size D50 of 9 μm is added to 500 g of hydrogen peroxide, stirred at 30° C. for 30 min, and then deionized water is added to terminate the reaction. The mixture is washed with water until neutral, and dried at 105° C. to obtain pre-oxidized graphite.

[0094] Comparative Example 1

[0095] The only difference from Example 1 is that the pre-oxidized graphite is replaced by unoxidized natural graphite.

[0096] Related performance testing methods

[0097] Particle size D50: 0.1 g to 0.2 g of the modified graphite negative electrode material prepared in Examples 1 to 7 and Comparative Example 1 was wetted with 0.1 mL of ethanol, and then water was added to 20 mL. The test was performed using a laser particle size analyzer. The measured results are shown in Table 1.

[0098] Specific surface area: The modified graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Example 1 were tested for specific surface area using a specific surface and porosity analyzer. The test standard referred to the national standard GB / T 19587-2017. The measured results are shown in Table 1.

[0099] Confocal Raman distribution value: Take the modified graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Example 1 as samples, use a confocal Raman spectrometer to test 2500 positions of each sample, and output the Raman values ​​I at 10%, 50%, and 90% respectively. 10 ,I 50 ,I 90 , confocal Raman distribution value = (I 90 -I 10 ) / I 50 The calculated results are shown in Table 1. This value can reflect the coating uniformity of the coating layer of the modified graphite negative electrode material. The smaller the value, the better the coating uniformity of the corresponding coating layer.

[0100] Oxygen content in pre-oxidized graphite: The oxygen content on the surface of pre-oxidized graphite was analyzed using a scanning electron microscope-energy dispersive spectrometer (SEM-EDS). The measured results are shown in Table 1.

[0101] Electrochemical performance test

[0102] The modified graphite negative electrode materials prepared in Examples 1 to 7 and Comparative Example 1 were used as negative electrode materials for batteries, and were uniformly mixed with SBR (styrene-butadiene rubber), CMC (sodium carboxymethyl cellulose), and SP (conductive carbon black) at a mass ratio of 95.5:2:1.5:1 to prepare a negative electrode active slurry, which was coated on a negative electrode current collector copper foil, dried, and rolled to prepare a negative electrode sheet, which was assembled with a metal lithium sheet into a button battery;

[0103] Under the conditions of 0.1C constant current charge and discharge and charge and discharge voltage of 0.05V-2.0V, the first charge and discharge capacity, first coulomb efficiency (first coulomb efficiency = first charge capacity / first discharge capacity*100%) and rate performance (rate performance = battery capacity at 1.2C / battery capacity at 0.05C*100%) of the button battery were tested; the measured results are shown in Table 1.

[0104] Table 1

[0105]

[0106] It can be seen from the data in Table 1 that compared with Comparative Example 1 in which the graphite was not pre-oxidized, the embodiment of the present application uses an amphiphilic carbon material that is both hydrophilic and lipophilic to coat and modify the pre-oxidized graphite, thereby improving the affinity between the amphiphilic carbon material and the pre-oxidized graphite. The amphiphilic carbon material coating layer of the modified graphite negative electrode material is more uniform and the electrochemical performance of the modified graphite negative electrode material is also better.

[0107] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a modified graphite negative electrode material, characterized in that: include: The amphiphilic carbon material solution and pre-oxidized graphite are kneaded, dried, and heat-treated to obtain a modified graphite negative electrode material precursor; The modified graphite negative electrode material precursor is carbonized to obtain the modified graphite negative electrode material.

2. The method for preparing the modified graphite negative electrode material according to claim 1, characterized in that: The oxygen content in the pre-oxidized graphite is 3%-10%.

3. The method for preparing the modified graphite negative electrode material according to claim 1 or 2, characterized in that: The mass of the amphiphilic carbon material in the amphiphilic carbon material solution is 1.5%-3% of the mass of the pre-oxidized graphite.

4. The method for preparing the modified graphite negative electrode material according to claim 1 or 2, characterized in that: The kneading is carried out at room temperature for 1 h to 2 h; And / or, a drying step is further included after the kneading and before the heat treatment.

5. The method for preparing the modified graphite negative electrode material according to claim 1 or 2, characterized in that: The heat treatment is a two-stage heat treatment; the temperature of the first stage of the two-stage heat treatment is 200°C-250°C, and the time is 2h-3h; the temperature of the second stage of the two-stage heat treatment is 500°C-550°C, and the time is 1h-2h.

6. The method for preparing the modified graphite negative electrode material according to claim 1 or 2, characterized in that: The temperature of the carbonization treatment is 1000° C.-1200° C., and the time of the carbonization treatment is 6 h-8 h.

7. The method for preparing the modified graphite negative electrode material according to any one of claims 1 to 6, characterized in that: The method for preparing pre-oxidized graphite comprises: pre-oxidizing graphite to obtain pre-oxidized graphite; And / or, the pre-oxidation treatment includes gas phase pre-oxidation treatment or liquid phase pre-oxidation treatment; The temperature of the gas phase pre-oxidation treatment is 600°C-700°C, and the time of the gas phase pre-oxidation treatment is 30min-60min; the flow rate of the oxidizing gas of the gas phase pre-oxidation treatment is 100mL / min-200mL / min, and the oxidizing gas includes one or more of air, oxygen and ozone; The temperature of the liquid phase pre-oxidation treatment is 20°C-40°C, and the time of the liquid phase pre-oxidation treatment is 30min-60min; the oxidant of the liquid phase pre-oxidation treatment includes one or more of concentrated sulfuric acid, concentrated nitric acid, hydrogen peroxide and perchloric acid; And / or, the particle size D50 of the graphite is 7 μm-15 μm; the specific surface area of ​​the graphite is 0.8 m 2 / g-3.0m 2 / g.

8. A modified graphite negative electrode material obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The modified graphite negative electrode material is a core-shell structure, comprising a graphite core and an amphiphilic carbon material coating layer coated on the surface of the graphite core.

9. A modified graphite negative electrode material as claimed in claim 8, characterized in that: The particle size D50 of the modified graphite negative electrode material is 10 μm-20 μm; and / or the specific surface area of ​​the modified graphite negative electrode material is 1 m 2 / g-2m 2 / g.

10. A negative electrode of a battery, characterized in that: It comprises a current collector and a negative electrode active layer loaded on the current collector, wherein the negative electrode active layer comprises a modified graphite negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or a modified graphite negative electrode material according to any one of claims 8 to 9.

11. A battery, characterized in that: The battery comprises a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, and the negative electrode comprises the battery negative electrode as claimed in claim 10.

12. An electrical device, characterized in that: The electric device comprises the battery as claimed in claim 11.